The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1155/2017/3876040
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants of Phyllanthus emblica L. Bark Extract Provide Hepatoprotection against Ethanol‐Induced Hepatic Damage: A Comparison with Silymarin

Abstract: Phyllanthus emblica L. (amla) has been used in Ayurveda as a potent rasayan for treatment of hepatic disorders. Most of the pharmacological studies, however, are largely focused on PE fruit, while the rest of the parts of PE, particularly, bark, remain underinvestigated. Therefore, we aimed to investigate the protective effect of the hydroalcoholic extract of Phyllanthus emblica bark (PEE) in ethanol-induced hepatotoxicity model in rats. Total phenolic, flavonoid, and tannin content and in vitro antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 41 publications
4
30
1
3
Order By: Relevance
“…Studies also showed that Monolluma quadrangula (Forssk.) Plowes, Geranium schiedeanum Schltdl., and Phyllanthus emblica L. are also effective in this respect (Ibrahim et al, 2015;Madrigal-Santillán et al, 2015;Chaphalkar et al, 2017). Recently a number of reviews have been published on the topic (Guan et al, 2018;Singh et al, 2018).…”
Section: Preclinical and Clinical Research Based On Ethnopharmacologimentioning
confidence: 99%
“…Studies also showed that Monolluma quadrangula (Forssk.) Plowes, Geranium schiedeanum Schltdl., and Phyllanthus emblica L. are also effective in this respect (Ibrahim et al, 2015;Madrigal-Santillán et al, 2015;Chaphalkar et al, 2017). Recently a number of reviews have been published on the topic (Guan et al, 2018;Singh et al, 2018).…”
Section: Preclinical and Clinical Research Based On Ethnopharmacologimentioning
confidence: 99%
“…In this group there was noted a significantly lower value of ALT and AST activity and alkaline phosphatase in the plasma compared to the group that received only 70% ethanol (10 ml/kg body weight per day). Furthermore, histopathological data showed hepatocyte damage with numerous areas of necrosis in the group of rats receiving ethanol while in the animals that did receive silymarin together with ethanol, the picture of liver parenchyma was correct with only minor inflammatory changes in a few hepatocytes without characteristics of necrosis [50]. Lieber et al [49] indicate that the cause of the differing results of various studies may be the application of silymarin in too small doses.…”
Section: Stosowanie Ekstraktu Sylimaryny W Alkoholowym Włóknieniu I Mmentioning
confidence: 99%
“…The researchers concluded that silymarin inhibits the development of liver fibrosis caused by ethyl alcohol consumption [49]. These results are in accordance with those of most recent studies by Chaphalkar et al [50] carried out with the aid of the animal damaged liver model in a group of rats receiving grupą a grupą kontrolną nieprzyjmującą sylimaryny. Autorzy podkreślają, że sylimaryna była dobrze tolerowana, ale choć odnotowano korzystne zmiany we krwi pacjentów (zmniejszenie stężenia MDA i aminokońcowego propeptydu prokolagenu typu III), to wyniki testów wątrobowych pozostały bez zmian [46].…”
Section: Stosowanie Ekstraktu Sylimaryny W Alkoholowym Włóknieniu I Munclassified
See 1 more Smart Citation
“…The phytoconstituents of plant extract possess antioxidative, anti-stress, appetite inducer and disease resistance properties (Chakraborty & Hancz, 2011;Citarasu, 2010;Mirghaed, Fayaz, & Hoseini, 2019). Emblica officinalis is easily available and economically viable plant, possessing antioxidative, hepatoprotective and immunostimulant properties (Chaphalkar, Apte, Talekar, Ojha, & Nandave, 2017;Hazra, Sarkar, Biswas, & Mandal, 2010;Tahir, Khan, Shah, & Aftab, 2016;Tan et al, 2018). Marker enzymes (serum glutamate oxaloacetate transaminase [SGOT], serum glutamate pyruvate transaminase [SGPT] and alkaline phosphatase [ALP]) are released in detectable concentration from damaged tissues in blood.…”
mentioning
confidence: 99%